Wastewater-based epidemiology for surveillance of infectious diseases in healthcare settings - Hassard, Francis; Bajón Fernández, Yadira; Castro-Gutierrez, Victor (Lippincott, Williams & Wilkins, 2023)
Purpose of review: Wastewater-based surveillance (WBS) (epidemiology) using near-source sampling (NSS) in large buildings, hospitals and care homes is reviewed covering three main areas: state-of-the-art WBS, benefits/opportunities NSS has for hospital infection control systems and new insights from hospital wastewater surveillance and policy implications. Recent findings: Wastewater provides aggregate, anonymous sources of data where the spatial resolution can be linked to populations being served. In hospitals, clear links established between wastewater RNA-fragments signal to nosocomial COVID-19 cases/outbreaks. Detecting other targets from hospital wastewater such as antimicrobial resistance markers is considered a substantial opportunity for this technology. Other clinically relevant infections, that is influenza and monkeypox, can be perceived, and sub-variant resolution to target public health response in near real time to benefit hospital infection control. WBS can reduce hospitals’ clinical testing requirements, as diagnostic costs are aggregated into fewer samples while still detecting single cases. Summary: WBS using NSS can inform infectious disease monitoring earlier, faster and cheaper than conventional monitoring. Routine sampling using wastewater provides a platform for risk-based sampling and enables smarter allocation of resources. Finally, hospital wastewater can be used for the benefit of the wastewater surveillance field as a promising source to monitor emerging threats and resolve longstanding questions on faecal shedding. Hospital monitoring in low-income settings is considered a priority for future research.
Keywords: COVID-19; hospital; infectious diseases; public health; risk management; SARS-CoV-2; wastewater-based epidemiology